2021
DOI: 10.1021/jacs.1c06414
|View full text |Cite
|
Sign up to set email alerts
|

Triple Resonance Experiments for the Rapid Detection of 103Rh NMR Shifts: A Combined Experimental and Theoretical Study into Dirhodium and Bismuth–Rhodium Paddlewheel Complexes

Abstract: A H(C)Rh triple resonance NMR experiment makes the rapid detection of 103 Rh chemical shifts possible, which were previously beyond reach. It served to analyze a series of dirhodium and bismuth–rhodium paddlewheel complexes of the utmost importance for metal–carbene chemistry. The excellent match between the experimental and computed 103 Rh shifts in combination with a detailed analysis of the pertinent shielding tensors forms a sound basis for a qualitative and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 71 publications
3
18
0
Order By: Relevance
“…Next, we directed our attention toward whether including an explicit axial ligand changes predictions about mechanism and/or energetics compared to using an implicit solvent model. Of the three solvents studied, we expect acetonitrile to have the most significant effects on reactivity, since it is the strongest σ-donor, 53,55,60 so we focus on it here first.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we directed our attention toward whether including an explicit axial ligand changes predictions about mechanism and/or energetics compared to using an implicit solvent model. Of the three solvents studied, we expect acetonitrile to have the most significant effects on reactivity, since it is the strongest σ-donor, 53,55,60 so we focus on it here first.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…56−59 Triple resonance NMR experiments confirmed that axial ligand coordination changes the chemical environment at the Rh nuclei, and the donor strength of a labile ligand is observed in 103 Rh chemical shift "deshielding". 60 Several directions have been explored to effect changes on dirhodium complexes by way of axial ligation, some of which are summarized below.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 38 , 39 Their drastic electronic impact has recently been demonstrated by means of 103 Rh NMR spectroscopy: thus, the rhodium atom of complex C6 bound to the amide N-atom resonates >1000 ppm upfield from its neighbor surrounded by O atoms only ( Figure 1 ). 40 Steric factors are unlikely to overcompensate the electronic effect: because an O atom and the −NH group are of similar size, access to either site of C1 is equally facile. However, complexes C5a , b demonstrate that the cyclopropanation at an [O 4 ]-face is much less enantioselective; therefore, any background reaction at this terminus of C1 would corrupt the ee.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Their drastic electronic impact has recently been demonstrated by means of 103 Rh NMR spectroscopy: thus, the rhodium atom of complex C6 bound to the amide N-atom resonates >1000 ppm upfield from its neighbor surrounded by O atoms only (Figure 1). 40 The −NH group must hence exert an effect that has gone unnoticed in the literature but which is capable of overriding the inherent electronic handicap imparted by the amide ligand. Hydrogen bonding could provide a plausible explanation: 1 thus, an incipient H bond between the −NH proton and the ester carbonyl of the incoming diazo derivative might help recruit the reagent to the [O 3 ,N] face as formally depicted in A and lower the barrier to carbene formation too (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Amongst the many catalyst systems that potentially qualify for this purpose, [31] the heterobimetallic bismuth‐rhodium paddlewheel complexes recently developed in our laboratory seem particularly adequate [32,33,34,35] . They owe their excellent performance to the following factors: the Bi(+2) site itself is incapable of converting diazo derivatives into carbenes but properly tunes the electronic character of the rhodium atom it is coordinated to [36,37] . At the same time, a multitude of stabilizing interligand London dispersion interactions [38,39] chiefly fostered by the peripheral silyl substituents on the phenylalanine‐derived ligands craft a narrow, conformationally well‐defined and highly ordered chiral binding site about the reactive rhodium center.…”
Section: Figurementioning
confidence: 99%